Design Space Exploration of Hard-Decision Viterbi Decoding: Algorithm and VLSI Implementation - Habib, Irfan; Paker, Ozgun; Sawitzki, Sergei (IEEE transactions on very large scale integration (VLSI) systems, 2010)
Viterbi algorithm is widely used as a decoding technique for convolutional codes as well as a bit detection method in storage devices. The design space for VLSI implementation of Viterbi decoders is huge, involving choices of throughput, latency, area, and power. Even for a fixed set of parameters like constraint length, encoder polynomials and trace-back depth, the task of designing a Viterbi decoder is quite complex and requires significant effort. Sometimes, due to incomplete design space exploration or incorrect analysis, a suboptimal design is chosen. This work analyzes the design complexity by applying most of the known VLSI implementation techniques for hard-decision Viterbi decoding to a different set of code parameters. The conclusions are based on real designs for which actual synthesis and layouts were obtained. In authors' view, due to the depth covered, it is the most comprehensive analysis of the topic published so far.